2010
DOI: 10.1074/jbc.m109.033399
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Inhibition of Histone Deacetylase 8 by Monovalent Cations

Abstract: The metal-dependent histone deacetylases (HDACs) catalyze hydrolysis of acetyl groups from acetyllysine side chains and are targets of cancer therapeutics. Two bound monovalent cations (MVCs) of unknown function have been previously observed in crystal structures of HDAC8; site 1 is near the active site, whereas site 2 is located >20 Å from the catalytic metal ion. Here we demonstrate that one bound MVC activates catalytic activity (K 1/2 ‫؍‬ 3.4 mM for K ؉ ), whereas the second, weakerbinding MVC (K 1/2 ‫؍‬ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(149 citation statements)
references
References 32 publications
9
138
1
Order By: Relevance
“…2B). The HDAC8 H143A mutant has an almost complete loss of activity in contrast to the residual activity of an H142A mutant, in concordance with the proposed model of action (Gantt et al 2010). Furthermore, quantum mechanical/molecular mechanical molecular dynamics simulations suggest that a neutral H143 first serves as the general base to accept a proton from the zincbound water molecule in the initial rate-determining nucleophilic attack step, and then shuttles it to the amide nitrogen atom to facilitate the cleavage of the amide bond (Wu et al 2011).…”
Section: Catalytic Mechanisms and Structuressupporting
confidence: 59%
“…2B). The HDAC8 H143A mutant has an almost complete loss of activity in contrast to the residual activity of an H142A mutant, in concordance with the proposed model of action (Gantt et al 2010). Furthermore, quantum mechanical/molecular mechanical molecular dynamics simulations suggest that a neutral H143 first serves as the general base to accept a proton from the zincbound water molecule in the initial rate-determining nucleophilic attack step, and then shuttles it to the amide nitrogen atom to facilitate the cleavage of the amide bond (Wu et al 2011).…”
Section: Catalytic Mechanisms and Structuressupporting
confidence: 59%
“…Of note, the crystal structures of several histone deacetylases identified a K ϩ ion in their structure (5,31). Furthermore, K ϩ regulates the activity of histone deacetylase 8, rendering this enzyme's activity sensitive to changes in the cellular K ϩ concentration (8). Interestingly, we have shown that LLO-mediated dePH3 correlates with a deacetylation of histone H4, and therefore, the two events could be linked (11).…”
Section: Discussionmentioning
confidence: 94%
“…These residues are less conserved than those of site 1 ( Figure S1 in the supplementary material online). The role of these two metal binding sites was investigated in HDAC8 [65] and found to be associated with enzyme activation or inhibition. Kinetic studies demonstrated that HDAC8 is inactive in the absence of added KCl or NaCl and that the enzyme shows higher activity when bound to K + rather than to Na + , the former ion being generally more abundant than the latter in the cellular cytoplasm.…”
Section: Additional Metal-binding Sitesmentioning
confidence: 99%